Modelling and Simulation of the Effect of Irradiance Related Temperature on Microalgae Cell Growth in an Outdoor Culture for a Horizontal Loop Tubular Photobioreactor (Contemporary Mathematics, 2025)
Microalgae growth is influenced by numerous culture parameters, and temperature is considered one of the vital growth factors among them. In this study, a computational growth model related for a microalgae cell growth to irradiance related temperature for an outdoor operated Horizontal Loop Tubular Photobioreactor (HLTP) is developed. The effects of direct and diffuse solar radiation on the Photobioreactor (PBR) temperature are considered in this model. An HLTP measuring length 20.5 m and radius 0.025 m has been assumed for the simulation model. The simulation is carried out on a specific date where the sunlight is considered available. Thus, the meteorological data associated with a geographic location has been collected for the simulation while the species of microalgae is Chlorella vulgaris. The present model is simulated by COMSOL Multiphysics version 4.2 and a temperature fluctuation between 24.85 °C and 38.45 °C is observed throughout the PBR domain. The velocity profile of the suspension flow is also analysed in this study. The present study suggests that necessary measures are needed to control the temperature to reduce cell damage.
Keywords: microalgae; biofuel; photobioreactor; solar irradiance; temperature